Material didáctico reciclado para la enseñanza de las Ciencias Naturales, subnivel medio, Escuela de Educación Básica Esmeraldas, cantón Sozoranga, periodo 2021-2022. - Lapo Gómez, John Jairo (2022)
The general objective of the Curricular Integration Work called: Recycled didactic material for teaching, was as follows: To determine in what way the didactic resources elaborated with recycled material have an impact on the teaching of Natural Sciences, middle level of the School of General Basic Education Esmeraldas, canton Sozoranga, period 2021-2022, likewise it has as specific objectives; To develop a bibliographic review on the use and exploitation of recyclable materials as didactic resources for teaching Natural Sciences; To diagnose the different didactic resources that teachers use for teaching Natural Sciences at the intermediate level of the school of Basic Education Esmeraldas, Sozoranga canton, period 2021-2022; To elaborate a didactic guide that allows the teacher to improve the identified problem using recycled material as didactic resources, for the middle sub-level of the school of Basic Education Esmeraldas, canton Sozoranga, period 2021-2022; likewise, I worked with the different methods that helped me to direct my work to give foundation to the following postulates of the authors based on the same to infer criteria with the purpose of deepening the proposed topic. This study was conducted under a mixed qualitative-quantitative approach of descriptive, experimental and statistical type with the reality of the research problem. The techniques used were: direct observation and the questionnaire; the instruments: the survey. The population consisted of 11 students and 1 teacher, who helped me to elucidate the problem through a bank of questions related to the research topic. The use of recycled didactic material in the subject of Natural Sciences will allow to contribute significantly to the students to develop their creativity and imagination, in such a way that it will be a great contribution in teaching and much more in the learning of the students. Key words: Recycled didactic material, Natural Sciences, Model, didactic material.